Computational Studies on Biosynthetic Carbocation Rearrangements Leading to Quiannulatene: Initial Conformation Regulates Biosynthetic Route, Stereochemistry, and Skeleton Type. (11th October 2018) - Sato, Hajime; Mitsuhashi, Takaaki; Yamazaki, Mami; Abe, Ikuro; Uchiyama, Masanobu
Abstract: The results of quantum chemical calculations on the mechanism of the carbocation cascade of reactions in the biosynthetic pathways leading to the pentacyclic sesterterpenes quiannulatene and sesterfisherol provide reasonable answers to several persistent mechanistic questions in sesterterpene biosynthesis, including: 1) the reaction pathways of the multicyclic ring system construction and skeletal rearrangements, 2) the mechanism of triquinane skeleton formation, which requires more complicated rearrangements than previously proposed, 3) the stereochemistry of the final carbocation intermediate, and 4) the determining factor of biosynthetic selection for either 5/6/4/6/5 or 5/6/5/5/5 pentacyclic skeleton formation. This in‐depth mechanistic study on sesterterpene biosynthesis revealed that the shape of the final product and the type of triquinane skeleton formed are regulated by the stereochemistry and conformation of the common starting material, geranylfarnesyl diphosphate (GFPP).